2009
DOI: 10.1007/s00280-009-1101-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of BNP7787-mediated cisplatin nephroprotection: modulation of gamma-glutamyl transpeptidase

Abstract: The GGT xenobiotic metabolism pathway is postulated to be a major toxification pathway for cisplatin nephrotoxicity, and BNP7787 may play a novel and critical therapeutic role in the modulation of GGT activity. We further postulate that there are two general mechanisms for BNP7787-mediated nephroprotection against cisplatin-induced nephrotoxicity involving this pathway. First, the active BNP7787 pharmacophore, mesna, produces an inactive mesna-cisplatin conjugate that is not a substrate for the GGT toxificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Additionally, some BNP7787-derived mesna-disulfide heteroconjugates, formed as a result of the extracellular reactions between BNP7787 and physiological thiols or between BNP7787-derived mesna and physiological disulfides, have been shown to inhibit GGT and APN. 15,16 Results of the studies herein indicate that the amount of BNP7787-derived mesna detected in lysates isolated from human HK-2 cells incubated with BNP7787 (10 mM) increased as a function of increasing incubation time. Cells generally maintain a strongly reducing intracellular environment 14,30 ; therefore, we propose that once BNP7787 enters the cell, it is likely to be reduced to the free thiol form metabolite, mesna.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Additionally, some BNP7787-derived mesna-disulfide heteroconjugates, formed as a result of the extracellular reactions between BNP7787 and physiological thiols or between BNP7787-derived mesna and physiological disulfides, have been shown to inhibit GGT and APN. 15,16 Results of the studies herein indicate that the amount of BNP7787-derived mesna detected in lysates isolated from human HK-2 cells incubated with BNP7787 (10 mM) increased as a function of increasing incubation time. Cells generally maintain a strongly reducing intracellular environment 14,30 ; therefore, we propose that once BNP7787 enters the cell, it is likely to be reduced to the free thiol form metabolite, mesna.…”
Section: Discussionmentioning
confidence: 85%
“…In animal studies, Ormstad and Uehara 14 noted that transmembranal uptake of dimesna (BNP7787) is expected to require energy and involve an active transport mechanism; they demonstrated the uptake of BNP7787 in rat kidney perfusions and rat kidney cells. Additionally, in vitro, we have observed that BNP7787 and BNP7787-derived mesna-disulfide heteroconjugates can inhibit human γ-glutamyltranspeptidase (GGT) and aminopeptidase N (APN) enzymes 15,16 that are postulated to be important in converting cisplatin to a nephrotoxigenic species. [22][23][24][25][26][27][28][29] If there is metabolism and local action and/or local uptake of BNP7787 by renal tubular cells, it is likely that a protective mechanism exists, whereby BNP7787's disulfide bond is reduced to yield BNP7787-derived mesna, the reactive thiol (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In an additional phase III clinical trial, treatment with BNP7787 seemed to significantly improve 1-year survival of patients with advanced primary adenocarcinoma of the lung who were being treated with cisplatin and paclitaxel regimens in the first-line setting (36). Previous studies have suggested that BNP7787 seems to have significant cisplatin nephroprotective benefits (11,37,38,40,46,49,50). Based on data presented herein, we propose that BNP7787 interactions with MTP may be one mechanism through which BNP7787 may act to protect against taxane-or platinum-induced neurotoxicity by normalizing paclitaxel-induced hyperpolymerization of MTP and by forming BNP7787-derived mesna in vivo, which reacts with and inactivates the highly reactive monoaquocisplatin species.…”
Section: Discussionmentioning
confidence: 92%
“…Minimization of renal toxicity is essential to improve the effectiveness of cisplatin chemotherapy and the quality of life of patients (Hausheer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%